Ulcerative colitis relapse after Helicobacter pylori eradication in a 12-year-old boy with duodenal ulcer - Yuji Fujita (BMC, 2021)
Abstract Background Helicobacter pylori (H. pylori) prevalence is lower in patients with inflammatory bowel disease (IBD) than in those without IBD, suggesting that H. pylori plays a protective role in IBD. It has been reported that IBD may occur due to H. pylori eradication; however, it is unclear whether H. pylori eradication increases the incidence of IBD. Moreover, the effect of H. pylori eradication on IBD activity is unclear. Case presentation An 11-year-old boy diagnosed with ulcerative colitis (UC) was in clinical remission, with treatment involving 5-aminosalicylic acid. Fecal calprotectin (FC) level had decreased to 33.2 mg/kg, indicating mucosal healing. At age 12, he experienced epigastric pain on an empty stomach, which was relieved with dietary intake. His FC level was elevated without UC symptoms, such as diarrhea and bloody stools. He was diagnosed with H. pylori duodenal ulcer. H. pylori eradication (clarithromycin and amoxicillin for 7 days and a proton-pump inhibitor) led to symptom improvement the day after treatment initiation. However, he developed diarrhea and his FC level remained high despite improvement in duodenal ulcer symptoms and endoscopic findings of H. pylori eradication. Colonoscopy results indicated UC relapse. Conclusions H. pylori eradication may worsen UC activity. However, further studies are required as this case report involved only one pediatric patient with increased UC activity after H. pylori eradication.